2018
DOI: 10.1016/j.joule.2018.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Reversible, Full-Color Luminescence by Post-treatment of Perovskite Nanocrystals

Abstract: A fully reversible (CsPbCl 3 # CsPbBr 3 # CsPbI 3) post-treatment method of anion exchange for CsPbX 3 (X = Cl, Br, I) perovskite nanocrystals conducted with haloalkane solvent and nucleophile is presented. Through the control of anionexchange kinetics, the band gaps of nanocrystals are finely tuned covering the full wavelength region from 400 to 700 nm. The dissociation mechanism of haloalkane solvent with nucleophile is clearly explained with S N 2 chemical reaction to produce halide anions. With the post-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(45 citation statements)
references
References 25 publications
1
43
0
Order By: Relevance
“…Among the different forms of MHP, nanocrystals (NCs) of MHP are emerging as one of the most exciting optoelectronic materials by virtue of their excellent photophysical properties including tunable, direct bandgap [4], strong quantum confinement [5], high photoluminescence quantum yield [6,7], and tolerance to defects [8] to name a few. Thanks to the advancement in material engineering of perovskite NCs in terms of morphology, stoichiometric control, doping, and surface treatment [9][10][11][12][13][14], highperformance light-emitting devices with external quantum efficiency (EQE) of 23.4% and 23.0% have been achieved with MHP NCs for green and red emission, respectively [15,16]. Nevertheless, most of the peak efficiencies are often observed at relatively low current densities and correspondingly low brightness due to lack of surface protection [17].…”
Section: Introductionmentioning
confidence: 99%
“…Among the different forms of MHP, nanocrystals (NCs) of MHP are emerging as one of the most exciting optoelectronic materials by virtue of their excellent photophysical properties including tunable, direct bandgap [4], strong quantum confinement [5], high photoluminescence quantum yield [6,7], and tolerance to defects [8] to name a few. Thanks to the advancement in material engineering of perovskite NCs in terms of morphology, stoichiometric control, doping, and surface treatment [9][10][11][12][13][14], highperformance light-emitting devices with external quantum efficiency (EQE) of 23.4% and 23.0% have been achieved with MHP NCs for green and red emission, respectively [15,16]. Nevertheless, most of the peak efficiencies are often observed at relatively low current densities and correspondingly low brightness due to lack of surface protection [17].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, the PeQD‐X can change the bandgap even after the completion of synthesis by exchanging halide anions, thereby rendering the PeQD‐X suitable for LEDs. [ 7,8 ] Nedelcu et al. reported that the photoluminescence (PL) emission (red, green, and blue colors) of PeQD‐X solutions can be determined based on the ratio of halide anions.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we demonstrated a high quantum efficiency with distinguishable blue-emitting regions of 480, 470, and 460 nm using mixed-halide ion-pair ligands, di-dodecyl dimethyl ammonium bromide (DDAB) and di-dodecyl dimethyl ammonium chloride (DDAC) . For the blue emissions, the high amount of Cl anions is a critical problem in CsPbCl 3 NCs owing to their low stability. , Therefore, using chloride ions (Cl – ) induced from a ligand of DDAC, stable CsPbX 3 NCs can be reconstructed through a self-anion exchange based on the unique property of perovskite . Using this treatment, perovskite NCs showed a finely tuned emission wavelength toward the deep-blue region at near 460 nm with a passivation of the surface defect states through a coordination bonding with Cs + or Pb + , which are positively charged metals.…”
Section: Introductionmentioning
confidence: 99%